Career Succes Perception, Is that Important? - Diana Titik Widayati; Nazaruddin Malik (Journal of Career and Entrepreneurship, 2023)
This study proposes the factors that influence employees‘ career success in the manufacturing industry, the factors are mentoring, soft skills, and Self-efficacy. The research was carried out to examine employers’ opinions regarding the importance of mentoring, soft skills, and Self-efficacy in Batam. Data analysis use multiple regression and 100 respondent. Results show that Mentoring and Self-efficacy were not significantly related to career success. Only Soft skill (English, information technology, communication, and leadership) was significantly related to a successful career.